Algunos aspectos problemáticos sobre la terminación anticipada - Sánchez Torres, Alexander Germán (Pontificia Universidad Católica del Perú, 2024)
This paper discusses the challenges faced by the aggrieved party or civil actor in the processes of early termination in the Peruvian criminal system. The mandatory intervention of the aggrieved party in the negotiation phase can affect the efficiency sought by negotiated justice, which drives the proposal to limit this preliminary phase to negotiations between the prosecutor and the defendant. The author suggests that the aggrieved party’s intervention should be restricted to the hearing addressing exclusively civil reparation, thereby ensuring their right to be heard without obstructing the criminal process. However, this restriction could raise questions about the effective judicial protection of the aggrieved party. Finally, the author concludes that greater autonomy in the initial negotiation, along with compensatory measures for the aggrieved party would help balance expediency and justice in these processes, consolidating a more agile and equitable model of negotiated justice.

El presente trabajo desarrolla los desafíos en la participación del agraviado o actor civil en los procesos de terminación anticipada en el sistema penal peruano. La intervención obligatoria del agraviado en la fase de negociación puede afectar la eficiencia que busca la justicia negociada, lo cual impulsa la propuesta de limitar esta fase preliminar a una negociación entre el fiscal y el imputado. El autor plantea que la intervención del agraviado se limite a la audiencia para abordar exclusivamente la reparación civil, garantizando así su derecho a ser escuchado sin obstruir el proceso penal. No obstante, esta restricción podría suscitar interrogantes sobre la tutela judicial efectiva del agraviado. Finalmente, el autor concluye sugiriendo una mayor autonomía en la negociación inicial, junto con medidas compensatorias para el agraviado, contribuiría a equilibrar la celeridad y la justicia en estos procesos, consolidando un modelo de justicia negociada más ágil y equitativo.
Some problematic aspects of early termination
Keywords: Early termination; Negotiated justice; Criminal Procedure Code; Effective judicial protection; Right to defense; Terminación anticipada; Justicia negociada; Código Procesal Penal; Tutela judicial efectiva; Derecho de defensa; https://purl.org/pe-repo/ocde/ford#5.05.01